1978
DOI: 10.1136/bmj.1.6106.140
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum oestrogen concentrations in post-menopausal women taking oestrone sulphate and oestradiol.

Abstract: This study, like those reported from other transplant units, did not rely on historical controls but was a retrospective analysis of concurrently treated groups. Haybittle4 states that when there is a large difference between two groups in such an analysis the following criteria must be satisfied before acting on the result: the results should be supported by other, similar studies (our study is supported by those referenced and by others); there should be a logical explanation (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1979
1979
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…The recent studies of Anderson et al (1978) have confirmed our own observations (Jacobs et al 1977) that there is no difference in plasma oestrone and oestradiol concentrations during treatment with piperazine oestrone sulphate or oestradiol valerate. In both studies any increase in plasma oestradiol levels after ingestion of either oestrogen preparation was always associated with a much greater increase of plasma oestrone levels.…”
Section: Endocrine Effectsof Postmenopausal Oestrogen Therapysupporting
confidence: 72%
“…The recent studies of Anderson et al (1978) have confirmed our own observations (Jacobs et al 1977) that there is no difference in plasma oestrone and oestradiol concentrations during treatment with piperazine oestrone sulphate or oestradiol valerate. In both studies any increase in plasma oestradiol levels after ingestion of either oestrogen preparation was always associated with a much greater increase of plasma oestrone levels.…”
Section: Endocrine Effectsof Postmenopausal Oestrogen Therapysupporting
confidence: 72%
“…Since Premarin does not contain any unconjugated equilin or estrone, our results indicate that equilin sulfate and estrone sulfate are absorbed from the gut and converted to circulating equilin and estrone, respectively. These results agree with earlier reports (12,20,21) that estrone sulfate is rapidly absorbed from the gut and converted to estrone and estradiol.…”
Section: Discussionsupporting
confidence: 95%
“…It has been shown previously (21) that after the oral administration of estrone sulfate (1.5 mg) to postmenopausal women, the serum levels of estrone sulfate were over 30 times the concentration of estrone in the same serum samples. Similarly, the pretreatment levels of estrone (30-50 pg/ml) were between 30-50 times lower than the level of estrone sulfate (1-2 ng/ml) in these postmenopausal women (21). It has also been reported (24) that in normal postmenopausal women, 85% of the total estrone present in the serum is estrone sulfate.…”
Section: Discussionmentioning
confidence: 89%
“…Oestrone and oestriol are metabolites of 17p-oestradiol. High levels of oestrone and oestrone sulphate have been found after the administration of 17P-oestradiol valerate (Anderson et al, 1978) or micronized 17Poestradiol (Dada et al, 1978). But 17P-oestradiol also has a higher affinity for oestrogen receptor sites than oestrone (Siiteri, 1975) and thus the value of adding oestriol is questionable.…”
Section: Table I Main Reasons For Drop-out For All Patients and Monthmentioning
confidence: 99%